Detection of Bovine and Porcine Adenoviruses for Tracing the Source of Fecal Contamination - Maluquer de Motes, Carlos (American Society for Microbiology, 2004)
In this study, a molecular procedure for the detection of adenoviruses of animal origin was developed to evaluate the level of excretion of these viruses by swine and cattle and to design a test to facilitate the tracing of specific sources of environmental viral contamination. Two sets of oligonucleotides were designed, one to detect porcine adenoviruses and the other to detect bovine and ovine adenoviruses. The specificity of the assays was assessed in 31 fecal samples and 12 sewage samples that were collected monthly during a 1-year period. The data also provided information on the environmental prevalence of animal adenoviruses. Porcine adenoviruses were detected in 17 of 24 (70%) pools of swine samples studied, with most isolates being closely related to serotype 3. Bovine adenoviruses were present in 6 of 8 (75%) pools studied, with strains belonging to the genera Mastadenovirus and Atadenovirus and being similar to bovine adenoviruses of types 2, 4, and 7. These sets of primers produced negative results in nested PCR assays when human adenovirus controls and urban-sewage samples were tested. Likewise, the sets of primers previously designed for detection of human adenovirus also produced negative results with animal adenoviruses. These results indicate the importance of further studies to evaluate the usefulness of these tests to trace the source of fecal contamination in water and food and for environmental studies.